Incorporation of Andriy Melnyk’s OUN into the Kharkiv Environment (1941–1943) - Diakova, Helena; Topchiі Daniil (Faces of War, 2025)
Today, studying the spread of OUN activities, particularly those of the OUN(m), in Eastern Ukraine during the German-Soviet War is particularly relevant. This paper aims to highlight the work of the OUN(m) in Kharkiv during the Nazi occupation. Analysing the available sources and publications, it can be stated that during the German-Soviet war, the OUN(m) took the opportunity to spread their ideology in the Eastern Ukrainian lands, creating their cells among the local population. The primary tasks of the OUN(m), who arrived in Kharkiv with the Germans as part of a Sonderkommando or propaganda groups, were to infiltrate the local administration, police, and cultural and educational institutions; propagate nationalist ideas about creating an independent Ukrainian state; and organise local cells. To do this, they used both legal and illegal methods. Bohdan Konyk, Yakiv Kravchuk, and Petro Sahaidachnyi were particularly prominent in Kharkiv. The peak of OUN(m) activity in the city was October–December 1941. This was due to their proximity to the Germans and the ability to conduct their work legally. During the Nazi Occupation, the ideological views of the OUN(m) in Kharkiv were transformed to adapt to a more moderate Eastern Ukrainian version of nationalism. Nevertheless, their ideas became known to the wider Kharkiv community, influencing the vision of Ukraine’s future among local nationalists.